Orthoflavivirus infection and the mTOR signaling pathway - Zhang, Yahui; Ba, Jianbo; Luan, Jie; Qi, Zhongtian; Liu, Bin (Frontiers in Microbiology, 2025)
Each year, mosquito-borne orthoflaviviruses, including Zika virus, dengue virus, and the Japanese encephalitis virus, threaten the health of more than 400 million people worldwide. To date, knowledge about the pathogenic mechanisms underlying orthoflavivirus infection and the interactions of these viruses with host cells is limited. Mammalian target of rapamycin (mTOR) is pivotal for cell growth and metabolism. The downstream targets of mTOR regulate protein translation and cell autophagy to affect orthoflavivirus replication, and its upstream protein AKT performs similar functions. In this work, the mechanism underlying the relationship between the mTOR signaling pathway and orthoflavivirus infection was reviewed from three perspectives: orthoflavivirus structure and life cycle, mTOR structure and signaling pathway, and regulation of the mTOR signaling pathway during orthoflavivirus infection.